Poetics of mu. Issue 6 (2nd June 2020) - Han, Sora
ABSTRACT: The daughter appears in Hortense Spillers's literary criticism as an oblique subject of a doubled law of genealogy: first, the Oedipal 'law of the Father' which intervenes on the mother–child relation and structures genealogical descent; and second, the law of a specific form of slave law, partus sequitur ventrem, which negates the paternity of both the white master and the black slave in establishing that a mother's slave status would be passed down to her child. How can we witness the operations of both the law of the Father, which confers symbolic legitimacy in exchange for observing the incest taboo; and the law of slavery, which implicitly sanctions incest precisely because it casts slave offspring outside the pale of human sexuality, and thus, symbolic legitimacy, in the first instance? This article offers the 'poetics of mu' – a form of writing cut by the structural diglossic haunt of slavery on language, sexuality and history – as a deeper way to think from the locus of a unique form of structural anonymity which radically unravels the laws of genealogy.